2015
DOI: 10.1021/acs.jpclett.5b01060
|View full text |Cite
|
Sign up to set email alerts
|

In Search for the Best Environment for Single Molecule Studies: Photostability of Single Terrylenediimide Molecules in Various Polymer Matrices

Abstract: Photobleaching is the main limiting factor in single molecule studies by optical techniques. We investigated the dependence of photostability of terrylene diimide (TDI) derivative on its environment using confocal fluorescence microscopy. Seven different polymers were tested. Depending on the matrix, photobleaching quantum yields vary by 2 orders of magnitude. Their values correlate with parameters characterizing oxygen mobility in polymers: diffusion coefficient and permeability. Poly(vinyl chloride) (PVC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…The corresponding average "on" times are then 42 sec, 35 sec, and 29 sec, respectively, which are consistent with differences in oxygen permeability and diffusion coefficients in these matrices, with, for example, PMMA having these parameters lower than PS by more than an order of magnitude, which renders it a much better matrix for single-molecule fluorescence spectroscopy. 21 Additionally, the percentage of molecules that exhibit blinking (i.e. reversible as opposed to irreversible degradation at the 100 sec time scale of the experiment) increased from 13% in PMMA to 20% in PS.…”
Section: Single Molecule Spectroscopy: Experimentsmentioning
confidence: 96%
“…The corresponding average "on" times are then 42 sec, 35 sec, and 29 sec, respectively, which are consistent with differences in oxygen permeability and diffusion coefficients in these matrices, with, for example, PMMA having these parameters lower than PS by more than an order of magnitude, which renders it a much better matrix for single-molecule fluorescence spectroscopy. 21 Additionally, the percentage of molecules that exhibit blinking (i.e. reversible as opposed to irreversible degradation at the 100 sec time scale of the experiment) increased from 13% in PMMA to 20% in PS.…”
Section: Single Molecule Spectroscopy: Experimentsmentioning
confidence: 96%
“…For single‐molecule fluorescence studies in polymer films, choosing an appropriate environment is crucial. It was demonstrated that photodegradation quantum yields of terrylene diimide vary by two orders of magnitude depending on the polymer matrix [13] . The highest photostability was observed for polymers that exhibit the lowest oxygen mobility.…”
Section: Introductionmentioning
confidence: 99%
“…This dye belongs to the rylene family [28], which is formed by extending the π-conjugated core system of highly fluorescent perylene-3,4:9,10-tetracarboxdimides. The rylene dyes have unique optical properties, such as high extinction coefficients, high thermal, chemical and photochemical stabilities, and exhibit brilliant colors [2930]. Furthermore, in bulk samples, TDI demonstrates an excellent fluorescence quantum yield (ca.…”
Section: Introductionmentioning
confidence: 99%